Sacred Landscapes of Hittites and Luwians Proceedings of the International Conference Florence, February 6th-8th 2014 in Honour of Franca Pecchioli Daddi - D'AGOSTINO, Anacleto; Orsi, Valentina; TORRI, GIULIA (Studia Asiana, 2015)
This book contains studies on the symbolic significance of the landscape for the communities inhabiting the central Anatolian plateau and the Upper Euphrates and Tigris valleys in the 2nd-1st millennia BC. Some of the scholars who attended to the international conference Sacred Landscapes of Hittites and Luwians held in Florence in February 2014, present here contributions on the religious, symbolic and social landscapes of Anatolia between the Late Bronze Age and Iron Age. Archaeologists, hittitologists and historians highlight how the ancient populations perceived many elements of the environment, like mountains, rivers and rocks, but also atmospheric agents, and natural phenomena as essential part of their religious and ideological world. Analysing landscapes, architectures and topographies built by the Anatolian communities in the second and first millennia BC, the framework of a symbolic construction intended for specific actions and practices clearly emerges.